IMPLEMENTATION OF GOOD GOVERNANCE BUSINESS SHARIA (GGBS) IN ISLAMIC BANKING IN INDONESIA - R. Juli Moertiono; Muhammad Syahbudi; Saparuddin Siregar (Institut Agama Islam Negeri Padangsidimpuan, 2021)
In the development of Sharia banking with the merger of several Sharia Banks to become Bank Indonesia Shariah (BIS), is hoped that it can progress very rapidly, as is the case of Islamic banking in Indonesia which has grown significantly. The development of Sharia banking must be accompanied by good governance so that it is not only a tag line for Islamic financial institutions. The Standard Operating Procedure of Islamic banking must be carried out properly based on Sharia principles. Therefore, Bank Indonesia issued Bank Indonesia Regulation No. 11/33/ PBI 2009 concerning the Implementation of Sharia Business Governance (GGBS) for Sharia Commercial Banks (BUS/ Bank Umum Syariah) and Sharia Business Units (UUS/ Unit Usaha Syariah). The five principles are: Transparency, Accountability, Responsibility, Professionalism and Fairness or equality. GGBS is a banking management system designed to improve compliance with the prevailing moral ethics laws and regulations. According to Chapra, the implementation of Good Corporate Governance is a requirement for Sharia Banks to develop properly and in accordance with Sharia compliance. The implementation of GGBS in Sharia banking is expected to create a business that is healthy, conducive, transparent and efficient and a blessing.